Mitochondrial electron transport chain in macrophage reprogramming: Potential role in antibacterial immune response - Manmohan Kumar; Shagun Sharma; Jai Kumar; Sailen Barik; Shibnath Mazumder (Current Research in Immunology)
Macrophages restrain microbial infection and reinstate tissue homeostasis. The mitochondria govern macrophage metabolism and serve as pivot in innate immunity, thus acting as immunometabolic regulon. Metabolic pathways produce electron flows that end up in mitochondrial electron transport chain (mtETC), made of super-complexes regulating multitude of molecular and biochemical processes. Cell-intrinsic and extrinsic factors influence mtETC structure and function, impacting several aspects of macrophage immunity. These factors provide the macrophages with alternate fuel sources and metabolites, critical to gain functional competence and overcoming pathogenic stress. Mitochondrial reactive oxygen species (mtROS) and oxidative phosphorylation (OXPHOS) generated through the mtETC are important innate immune attributes, which help macrophages in mounting antibacterial responses. Recent studies have demonstrated the role of mtETC in governing mitochondrial dynamics and macrophage polarization (M1/M2). M1 macrophages are important for containing bacterial pathogens and M2 macrophages promote tissue repair and wound healing. Thus, mitochondrial bioenergetics and metabolism are intimately coupled with innate immunity. In this review, we have addressed mtETC function as innate rheostats that regulate macrophage reprogramming and innate immune responses. Advancement in this field encourages further exploration and provides potential novel macrophage-based therapeutic targets to control unsolicited inflammation.